Electrochemical corrosion evaluation of pure, carbon-coated and anodized Al foams. (February 2015) - Stergioudi, F.; Vogiatzis, C.A.; Gkrekos, K.; Michailidis, N.; Skolianos, S.M.
Highlights: Conventional anodizing and carburizing is applied to open-cell Al foam. Structural characteristics of the foams were examined by X-ray computed tomography and SEM. Corrosion behavior was tested experimentally, by polarization curves and EIS. Corrosion mechanisms along with appropriate modeling circuits were deduced. Abstract: Conventional anodizing and carbon deposition coating treatment is applied to open-cell Al foams aiming to enhance the corrosion performance of the material. The Al foams used were fabricated utilizing a dissolution-sintering technique based on powder metallurgy route. X-ray computed tomography and SEM were utilized to assess the structural characteristics of the produced foams. The corrosion properties of all samples produced were assessed experimentally, employing both polarization curves and EIS measurements utilizing a 0.6 M NaCl aqueous solution. Corrosion mechanisms along with appropriate modeling circuits were deduced. Both anodizing and carbon coatings resulted in an augment of the corrosion properties of the Al foams.